APLIKASI PERHITUNGAN RESISTOR SMD BERBASIS ANDROID - Setiawan, Ade; Maulana, Andry; Faisal, Muhamad; Pernando, Frenki (Jurnal Akrab Juara, 2019)
In this study, how to create an SMD resistor application that aims to help mobile phone technicians who experience problems in reading an SMD resistor value whose size is as large as fleas. This is because the SMD resistor has unique codes to determine the value of a component that is not easily memorized for mobile and computer repair technicians, thus influencing the effectiveness and speed of work of mobile phone technicians. For the tools used in making this application include the Indigo Eclipse, Android Windows SD, UML and Flowchart.